A clear trade-off exists between the theoretical efficiency and acceptability of dietary changes that improve nutrient adequacy during early pregnancy in French women: Combined data from simulated changes modeling and online assessment survey - Bianchi, Clélia M. (PLoS One, 2018)
BACKGROUND: During pregnancy, the diet of a mother-to-be should be adapted to meet increases in nutrient requirements. We analyzed the theoretical efficiency and acceptability of different types of tailored dietary changes for pregnant women. METHODS: The nutrient adequacy of the diet was evaluated using the PANDiet score, by comparing the nutrient intakes of 344 non-pregnant premenopausal women (18–44y) with dietary reference intakes for the first trimester of pregnancy. Simulations were performed to evaluate the theoretical efficiency of three types of ten successive tailored dietary changes in improving nutrient adequacy, with graded difficulty in implementation. The acceptability (declared intention to use in the diet) of most efficient dietary changes was evaluated during an online randomized study including 115 French pregnant women (22–41y). RESULTS: Modifying the amount consumed of foods (type-1) did not modify the food repertoire and resulted in the smallest theoretical efficiency (increase in the PANDiet score of 9.8±0.2 points), but changes were the most acceptable (probability of the intention to use: 0.30–0.78). Conversely, replacing food items by items from the same group or eaten at the same time (type-3) broadened the food repertoire (3.6±1.3 food subgroups added) and resulted in the greatest theoretical efficiency (+23.9±0.3) but changes were the least acceptable (0.07–0.23). Replacing food items within the same subgroup (type-2) slightly broadened the food repertoire (+8.0±1.3 foods) and resulted in moderate theoretical efficiency (+14.8±0.2) and intermediate acceptability (0.11–0.35). CONCLUSION: A clear trade-off exists between the theoretical efficiency and acceptability of dietary changes, with a graded broadening of the food repertoire.